Optimization of the method for synthesis of methylated poly-5-vinyltetrazole - Scherbakova, Olga S.; Grigoriev, Yuri V.; Zuraev, Alexander V.; Grigorieva, Inna M.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2019)
Optimization of the method for the synthesis of methylated poly-5-vinyltetrazole was carried out and it was shown that the process of its preparation, both with the homopolymer acrylonitrile and the commercially available copolymer with methyl acrylate and 2-acrylamido-2-methylpropane sulfonic acid, as starting materials, can be carried out in a single-step apparatus without intermediate release of poly-5-vinyltetrazole. At the same time, the resulting product is identical in composition, structure, and properties to that obtained using a two-stage process. Ability to refuse intermediate release of poly-5-vinyltetrazole allows to reduce the amount of dimethylformamide required for the preparation of methylated poly-5-vinyltetrazole twice, exclude the use of HCl solution from the process, and significantly reduce the time and energy costs of the process.
Keywords: poly-5-vinyltetrazole methylated; one-stage instrumental synthesis method